USE OF EPISIOTOMY AMONG RESIDENTS IN OBSTETRIC NURSING - Érica Silva Rocha; Camila Casagrande Mela; Flavia Westphal; Rosely Erlach Goldman (Universidade Federal do Paraná, 2018)
Objective:to identify the frequency of and justification for episiotomy in childbirths attended by residents in obstetric nursing. Method:Descriptive and retrospective study conducted in October-November, 2016, in a public maternity hospital in the city of São Paulo. The study population consisted of 884 low-risk pregnant women. Chi-square testwas used for statistical analysis. Results:Episiotomy was performed in 174 (19.7%) deliveries and in 512 (59%) there were perineal lacerations. Perineal integrity was maintained in 187 (21.4%) deliveries. The main indications were related to perineal conditions: 54 (58.1%) perineal rigidity, 22 (23.7%) short perineum and 19 (20.4%) imminent severe laceration.Conclusion:The frequency of use of episiotomyby residents in obstetric nursingis higher than evidence based recommendations from the WHO, and regarding the reasons for the procedure, they differ from those generally reported worldwide, which leads to reflections about the model of professional training of obstetric nurses and the distance between theory and practice.